A new system surveys for efficiently acquiring vertical seismic profile. Issue 1 (1st December 2018) - Dean, Tim; Nguyen, Nghia; Armitage, Brenton; Rossiter, Huw
Abstract : A vertical seismic profile (VSP) survey involves placing sensors in a borehole to record the passage of energy transmitted using a source of seismic energy placed on the surface. The sensors are usually contained within sondes that are coupled to the borehole wall using mechanical clamps. Existing VSP acquisition systems are generally unsuitable for acquisition using the wireline units typically used for minerals logging. In this paper we describe a new multis-sonde VSP acquisition system specifically designed for acquiring high-resolution VSP surveys in hard-rock environments.